ABO-incompatible Pediatric Liver Transplantation With Antibody and B-cell Depletion-free Immunosuppressive Protocol in High Consanguinity Communities. Issue 12 (4th November 2022) - Shagrani, Mohammad; Kumar, Kishwer; Baker, Alastair; Al-Awwami, Moheeb; Alhussaini, Hussa; Almanea, Hadeel; Alhumaidan, Hind; Iorio, Raffaele; Al-Khabbaz, Hana; Burdelski, Martin; Troisi, Roberto I.; Broering, Dieter C.
Abstract : Background: The success of orthotopic liver transplantation as a life-saving treatment has led to new indications and a greater competition for organ grafts. Pediatric patients with acute liver-related crises can benefit from orthotopic liver transplantation, but organ availability in the limited time can be a major obstacle. Crossing ABO blood group barriers could increase the organs available to such patients Methods: From November 2010 to June 2015, 176 children aged 0.2−to18 y were transplanted in the King Faisal Specialist Hospital and Research Center. Out of those, 19 children were transplanted across blood group barriers (ABO incompatible). The underlying diseases were biliary atresia (n = 6); progressive familial intrahepatic cholestasis type 2 (n = 4); Crigler-Najjar syndrome (n = 3); hepatoblastoma (n = 2); and urea cycle disorder, Caroli disease, cryptogenic cirrhosis, and neonatal sclerosing cholangitis (n = 1 each). Immunosuppression consisted of basiliximab, mycophenolate, tacrolimus, and steroids. Pretransplant prophylactic plasmapheresis, high-dose immunoglobulins, and rituximab were not administered. Results: The grafts were from living donors (n = 17) and deceased donors (n = 2). Living donor morbidity was nil. The recipient median age was 21 mo (5−70 mo). After a median follow-up of 44 mo, 2 recipients (10%) died because of sepsis, 1 because of uncontrolled acute myeloid leukemia. The overall rejection rate was 7%, and no grafts were lost because of antibody-mediated rejection (AMR). HLA matching was 3.8 of 6 (A, B, DR), and there were 2 patients presented with acute cellular rejection, 1 patient with AMR, and 1 patient with biliary strictures. Conclusions: ABO incompatible liver transplantation is a feasible and life-saving option even with antibody and B-cell depletion-free protocol without increasing the risks for AMR. We speculate that this excellent result is most likely because of presence of relatively low titer ABO isoagglutinins and the high HLA match compatibility caused by habit of longstanding interfamilial marriages as typical of Saudi Arabia.